New technology-based firms in the new millennium. Vol. 8 - Oakey, R. P. (Emerald, 2010)
The New Technology-Based Firms in the New Millenium series provides up to date research on a variety of aspects of High Technology Small Firm formation and growth (HTSFs) from a range of interdisciplinary perspectives and from national contexts throughout the world. This edited book series reflects on and shapes currently popular national government policies insofar as they relate to HTSFs. It is the only international publication specifically dealing with HTSF formation and growth and it uniquely provides an uninterrupted record of research in this area since 1993. This latest volume is a collection of the best papers presented at the HTSF Conference held in the United Kingdom at Manchester Business School in June 2007. Three major themes have emerged. Six particularly strong chapters of this volume are devoted to the critical problems of HTSF financing, comprising two contributions from the United Kingdom and individual chapters from Sweden, the Irish Republic, Italy, and Belgium. A further four papers are concerned with aspects of strategic development in HTSFs, and a final group of three papers deal with HTSF marketing problems, often in a strategic context.
Keywords: High technology industries.; New business enterprises -- Effect of technological innovations on.; elektronické knihy; electronic books